Bone marrow‐derived mononuclear cell therapy for nonischaemic dilated cardiomyopathy—A meta‐analysis. (11th February 2018) - Wen, Yanting; Ding, Jingjing; Zhang, Bin; Gao, Qian
Abstract: Objective: The therapeutic effects of bone marrow‐derived mononuclear cells (BMMNCs) transplantation in patients with nonischaemic dilated cardiomyopathy (DCM) are still under debate. Current randomized controlled trials (RCTs) reported conflicting results. The aim of this study was to assess the effects of BMMNCs transplantation on left ventricular ejection fraction (LVEF) in patients with nonischaemic DCM. Methods: A comprehensive search of PubMed, EMBASE and Cochrane Controlled Trials Register was performed. We included RCTs reporting data on LVEF in patients with nonischaemic DCM after BMMNCs transplantation. Results: Seven RCTs including 463 patients were included. BMMNCs transplantation significantly improved LVEF by 3.79% (95% CI: 0.56%‐7.03%; P = .007) and LVESV by −24.36 mL (95% CI: −46.36 to −2.36 mL; P = .03), while had no impact on the risk of all‐cause death (OR 0.92; 95% CI: 0.41 to 2.08%; P = .84). Subgroup analysis demonstrated a more significant improvement of LVEF in patients with longer follow‐up ( 15 months to 5 years) than shorter ones (12 months). Moreover, using bone marrow mononuclear cells was more effective than using G‐CSF‐stimulated bone marrow/peripheral blood stem cells in the improvement of LVEF in patients with nonischaemic DCM. Conclusions: Bone marrow‐derived mononuclear cells transplantation is associated with a moderate, but significant, improvement in LVEF in patients with nonischaemic DCM. This meta‐analysis supports further RCT conductions using BMMNCs transplantation with larger patient's population and longer term follow‐up.